2010
DOI: 10.1007/s12020-010-9368-7
|View full text |Cite
|
Sign up to set email alerts
|

Disappearing adrenal masses

Abstract: Adrenal incidentalomas are a common finding due to the increasing use and improved technology of imaging studies. The majority of these enlargements are non-functional and irreversible. Publications on reversible adrenal enlargement are sparse. Our patient, a 66-year-old man, was admitted to the hospital due to abdominal discomfort. He was treated for rectal carcinoma 3 years before, and was now free of disease. Computed tomography (CT) scan showed no abnormalities other than the incidental finding of bilatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…A retrospective study evaluating abdominal CT scans in patients with depression demonstrated that 12 out of 38 subjects had significantly increased adrenal volumes compared to normal controls (6). Nonfunctional reversible adrenal enlargement cases have been previously reported (7,8), suggesting hematomas, cystic lesions, and infections of adrenal glands as possible etiologies. Functional differentials include Cushing's disease with cyclical ACTH production, stress-induced ACTH-dependent adrenal hyperplasia, and ectopic ACTH production.…”
Section: Discussionmentioning
confidence: 98%
“…A retrospective study evaluating abdominal CT scans in patients with depression demonstrated that 12 out of 38 subjects had significantly increased adrenal volumes compared to normal controls (6). Nonfunctional reversible adrenal enlargement cases have been previously reported (7,8), suggesting hematomas, cystic lesions, and infections of adrenal glands as possible etiologies. Functional differentials include Cushing's disease with cyclical ACTH production, stress-induced ACTH-dependent adrenal hyperplasia, and ectopic ACTH production.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, in the resolution phase of the hypertrophy, the adrenal morphology, in our clinical case, was not typical for post-haemorrhagic evolution, as it showed neither cystic nor calcific involution [16] . Finally, bilateral cystic lesions are rare finding, which can be excluded due to the CT densitometry not compatible with fluid lesions [9] .…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted on rats, prolonged depressive-anxious stress induces the activation of the paraventricular hypothalamic nucleus, located at the apex of the HPA axis, resulting in bilateral adrenal hyperplasia downstream [20] . In literature, there are no data on acute stress as a cause for transient adrenal growth even though it is described a clinical case of bilateral adrenal incidentalomas (without hormonal overproduction) disappearing completely and spontaneously after 3 months [9] . The patient described was affected by ileus, developed erysipelas of the right foot with fever and chills during hospitalization.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation